A new self-consistent model for thermodynamics of binary solutions. (November 2015) - Svoboda, J.; Shan, Y.V.; Fischer, F.D.
Abstract : The newly developed self-consistent model exploits the trapping concept and calculates the numbers of A–A, A–B and B–B bonds in A–B alloys in dependence of the bond-energy parameter. Consequently the self-consistent model improves the classical regular solution model utilizing the assumption of random distribution of solute atoms. Remarkable differences between both models are demonstrated. The self-consistent model may significantly reduce the number of fitting parameters in the CALPHAD approach as well as experimental efforts.